PREDICTIVE FACTORS OF FUNCTIONAL MOBILITY IN OLDER WOMEN AFTER 12 WEEKS OF RESISTANCE TRAINING - More Torres Montalvão; Joana Marcela Sales de Lucena; Milene Soares Nogueira de Lima; Alexandre Lima de Araújo Ribeiro; Marisete Peralta Safons; Sarah Brandão Pinheiro; Wagner Rodrigues Martins (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To analyze the association between functional mobility, anthropometric and functional characteristics of older women after 12 weeks of resistance training. METHODS: This is a quasi-experimental descriptive study with a multiple linear regression analysis. A significance level of 0.05 was adopted. Forty-seven community-dwelling older women underwent 12 weeks of supervised resistance training twice a week. The dependent variable (mobility measured by the Timed Up and Go test) and the independent variables (age, body mass index, fat-free mass of the lower limbs, waist circumference, peak knee torque at 60º/s, peak knee torque at 180º/s, functional reach test, and 30-second chair stand test) were measured before and after the intervention. RESULTS: A multivariate analysis showed that age, body mass index, waist circumference, and the 30-second stand test predicted 30% (R2 = 0.30; p = 0.001; F = 5.53) of the total variance regarding an improvement in mobility after resistance training (p < 0.0001; [95% CI 0.72-1.20]; the effect size was considered large [0.90]) when comparing women before and after the intervention. CONCLUSIONS: Age, body mass index, waist circumference, and the 30-second stand test predicted 30% of the increase in functional mobility.